The Prognostic Value of Global Longitudinal Strain (GLS) in Predicting Outcomes in Coronary Artery Disease - Jason Wirandy Haryanto; Kevin Jonatan Sandi; Clement Panduwinata; Nathaniel Hiwandika (The International Journal of Medical Science and Health Research, 2025)
Introduction: Coronary artery disease (CAD) is a leading cause of morbidity and mortality worldwide. Global Longitudinal Strain (GLS) has emerged as a promising echocardiographic parameter for assessing left ventricular function and predicting clinical outcomes in CAD patients. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2015 to 2025. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, Semanthic Scholar, and Google Scholar. A systematic review of recent literature was conducted, focusing on studies that evaluated the prognostic value of GLS in CAD. Data were extracted regarding GLS measurements, clinical outcomes, and risk stratification. Results: The findings indicate that impaired GLS is significantly associated with adverse outcomes, including myocardial infarction, heart failure, and increased mortality. GLS provides incremental prognostic information beyond traditional measures such as left ventricular ejection fraction (LVEF), enhancing risk stratification in CAD patients. Discussion: GLS serves as a sensitive marker for detecting subclinical myocardial dysfunction, allowing for earlier intervention strategies. Its ability to predict adverse events underscores its potential role in routine clinical practice for managing CAD. Conclusion: GLS is a valuable tool in the assessment of cardiac function and risk stratification in patients with CAD. Incorporating GLS into clinical practice may improve patient outcomes through timely identification of high-risk individuals.